ЕТНІЧНИЙ СКЛАД НАСЕЛЕННЯ ХЕРСОНСЬКОЇ ГУБЕРНІЇ У 80-Х РОКАХ ХІХ СТ. ЗА МАТЕРІАЛАМИ ЗЕМСЬКИХ СТАТИСТИЧНИХ ОПИСІВ (Zaporizhzhia Historical Review, 2021)
In given article the author considers a problem of studying of national structure on the basis of materials of the description which was conducted in 1880th years by the zemstvo statisticians of Kherson province. Statistical descriptions are a valuable source of ethnic history, because they contain information on the number of basic national groups, allow to define the problems of study of national structure of population, characterize the ethnocultural interrelation between different national groups.